Designing Remedies to Compensate Plaintiffs for Unobservable Harms. (3rd September 2018) - Atkinson, Nathan
Abstract: Despite the vast sums transferred through the legal system, the foundations of the procedures used to compensate plaintiffs for unobservable losses remain unclear. Standard remedies can compensate plaintiffs for unknown harms, but it is expensive to do so. Damage awards will generally undercompensate or overcompensate a plaintiff whose true harm is unknown, while equitable remedies that provide more tailored compensation are generally wasteful. In this article I develop a novel remedy that compensates plaintiffs for unobservable private values at the lowest possible cost to the defendant. This remedy consists of offering the plaintiff the choice between intermediate damages and an inalienable injunction that restores the underlying harm at the conclusion of the trial. I show that this remedy is robust to errors by the court and potential post judgment renegotiation. Furthermore, I demonstrate that this remedy reduces litigants' incentives to lie during trial. Finally, I consider ex ante deterrence and show conditions under which the remedy improves social welfare relative to optimal damages.